Urban hassles and navigating education: Perceptions of urban high schoolers from a school-wide needs assessment - James P Canfield; Kennesha J Smith; Wendy L Wilson; Lauren Shute (International Journal of School Social Work, 2025)
A wealth of scholarly research examines the impact of school environments and climates on students, but far less attention is paid to how the school environment’s positioning within its larger community influences student experiences. While there is an understanding that outside environment influences what happens within the school, little study has been done to examine this from a student perspective. The purpose of this paper is to examine how the perceptions of urban high school students influence their navigation of the school environment, sense of empowerment, and future thinking. This study uses a dataset developed from a school-wide needs assessment conducted at an urban Midwestern high school. Findings include students from higher hassle environments perceived the school environment and their futures lower than their low-hassle experiencing peers. Study results posit schools may increasingly need to consider the impact of the proximal external environment when developing and implementing various policies and interventions to improve student outcomes in schools.
Keywords: urban hassles; school climate; school environment; urban schools